1999
DOI: 10.1038/sj.bjc.6690614
|View full text |Cite
|
Sign up to set email alerts
|

Different adhesion properties of highly and poorly metastatic HT-29 colon carcinoma cells with extracellular matrix components: role of integrin expression and cytoskeletal components

Abstract: Summary Integrin-mediated tumour cell adhesion to extracellular matrix (ECM) components is an important step in the development of metastatic lesions. Thus, integrin expression and integrin-mediated adhesion of colon carcinoma cells to various ECM components was examined. Poorly (HT-29P) and highly (HT-29LMM) liver-metastatic colon carcinoma cells were used to study the rates of adhesion to collagen I (C I), collagen IV (C IV), laminin (LN), fibronectin (FN), or vitronectin (VN) in a static adhesion assay (10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 56 publications
3
37
1
1
Order By: Relevance
“…This antibody reduced collagen adherence by 29% (Caco-2), 48% (HT-29), and 53% (MA104) for mock-infected cells and 38% (Caco-2), 57% (HT-29), and 39% (MA104) for RRV-infected cells. Adhesion of uninfected Caco-2 and HT-29 cells to type 1 collagen was similarly reduced by anti-␣2 antibodies in previous studies (33,36,50). Our experiments show this function is retained in rotavirusinfected cells.…”
Section: Rotavirus-induced Regulation Of Integrin Expression In Intessupporting
confidence: 68%
See 1 more Smart Citation
“…This antibody reduced collagen adherence by 29% (Caco-2), 48% (HT-29), and 53% (MA104) for mock-infected cells and 38% (Caco-2), 57% (HT-29), and 39% (MA104) for RRV-infected cells. Adhesion of uninfected Caco-2 and HT-29 cells to type 1 collagen was similarly reduced by anti-␣2 antibodies in previous studies (33,36,50). Our experiments show this function is retained in rotavirusinfected cells.…”
Section: Rotavirus-induced Regulation Of Integrin Expression In Intessupporting
confidence: 68%
“…The ␣2␤1, ␣V␤3, ␣V␤5, ␣5, and ␤2 integrins were chosen for analysis based on their predominance on rotavirus-permissive intestinal cells (33,36,42,50,74) and the role of a subset in rotavirus cell entry. It is demonstrated that rotavirus infection of intestinal cells differentially regulates rotavirus receptor and non-receptor integrin mRNA and protein expression by a PI3K-dependent pathway that is activated by infection.…”
mentioning
confidence: 99%
“…Due to an incomplete layer of hepatic ECs, these ECM components are directly accessible to circulating cells (16,18). Various studies have shown that interactions between these ECM components within the liver and tumor cells appear to be crucial to the formation of hepatic metastases (19)(20)(21). The liver is furthermore unique, since it lacks a basement membrane under the sinusoidal endothelium (22).…”
Section: Regulation By Circulation Patterns and Microvessels In Livermentioning
confidence: 99%
“…Several mechanisms are implicated in the process, including changes in adhesion properties that allow tumor cell detachment and migration (9,10). Adhesion of metastatic cells to the underlying extracellular matrix is very important (11), and the acquisition of metastatic competence by clones of cells with growth advantages is thought to be associated with an ability to coordinate the adhesive properties in every step of metastasis.…”
Section: Introductionmentioning
confidence: 99%